2020
DOI: 10.1002/dvdy.143
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal dye injection method for visualizing the functioning lymphatic vascular system in zebrafish and medaka

Abstract: A hierarchically organized lymphatic vascular system extends throughout the vertebrate body for tissue fluid homeostasis, immune trafficking, and the absorption of dietary fats. Intralymphatic dye injection and serial sectioning have been the main tools for visualizing lymphatic vessels. Specific markers for identifying the lymphatic vasculature in zebrafish and medaka have appeared as new tools that enable the study of lymphangiogenesis using genetic and experimental manipulation. Transgenic fishes have becom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Since LyVs readily absorbs cinnabar dye, the intraperitoneal injection of this dye into experimental animals allows visualization of lymphatic vessels in whole embryos or whole organs of adult animals in standard histological and transmission electron microscopy sections. 78 Based on the expression of Prox1, Lyve1, VEGFR-3, podoplanin, and other molecules in LEC, after whole-body immunostaining with specific antibodies to these molecules, the whole-body immunostaining and clarified tissue samples observed by light sheet microscopy presented important information about lymphatic vessels in 3-dimensional form (Figure 2). This technique can distinguish initial lymphangiectasia or degeneration from precollector or collector vessel changes in caliber or density, which have different functional effects on tissue drainage capacity.…”
Section: Visualization Techniques For Lymphatic Vasculature Molecular...mentioning
confidence: 99%
“…Since LyVs readily absorbs cinnabar dye, the intraperitoneal injection of this dye into experimental animals allows visualization of lymphatic vessels in whole embryos or whole organs of adult animals in standard histological and transmission electron microscopy sections. 78 Based on the expression of Prox1, Lyve1, VEGFR-3, podoplanin, and other molecules in LEC, after whole-body immunostaining with specific antibodies to these molecules, the whole-body immunostaining and clarified tissue samples observed by light sheet microscopy presented important information about lymphatic vessels in 3-dimensional form (Figure 2). This technique can distinguish initial lymphangiectasia or degeneration from precollector or collector vessel changes in caliber or density, which have different functional effects on tissue drainage capacity.…”
Section: Visualization Techniques For Lymphatic Vasculature Molecular...mentioning
confidence: 99%
“…Such studies have shown that zebrafish possess a lymphatic system that shares key structural and functional features with its mammalian counterpart [47,48]. Examples of functional similarities include the ability of zebrafish lymphatic vessels to clear injected dyes from extracellular spaces [9,[47][48][49][50] and the presence of collecting vessels with valves for unidirectional lymph flow [51].…”
Section: Techniques and Models To Visualise Lymphatics During Embryonmentioning
confidence: 99%
“…Overall, this caudal lymphatic network recapitulates the patterns described upon injection of red fluorescent beads to fli1-GFP transgenic lines (vascular and lymphatic endothelial cells) 38 or injection of cinnabar dye. 39 Interestingly, high resolution 3D imaging of the Tg (batf3MIN:eGFP) eGFP pattern in the tail of juveniles highlights the elusive "lymphatic heart" in vivo. These observations will therefore enable to conduct functional studies to unveil the functions of lymphatics in the caudal tissue during inflammation/regeneration processes modeled in zebrafish over development.…”
mentioning
confidence: 99%